The Routledge companion to health humanities - Crawford, Paul, 1963-; Brown, B. J. (Brian J.); Charise, Andrea (Routledge companions., 2020)
"The health humanities is a rapidly rising field, advancing an inclusive, democratizing, activist, applied, critical, and culturally diverse approach to delivering health and well-being through the arts and humanities. It has generated new kinds of interdisciplinary research, knowledge, and communities of practice globally. It has also acted to bring greater coherence and political force to contributions across a range of related disciplines and traditions. In this volume, a formidable set of authors explore the history, current state, and future of the health humanities, in particular how its vision of the arts and humanities: Promotes creative public health. Opens new routes to health and well-being. Informs and drives better health care. Interrogates relationships between ill health and social equality. Develops humanist theory in relation to health and social care practice. Foregrounds cultural difference as a resource for positive change in society. Tests the humanity of an increasingly globalized health-care system. Looks to overcome structural and process obstacles to cross-disciplinary ventures. Champions co-construction, co-design, and mutuality in solving health and well-being challenges. Showcases less familiar, prominent, or celebrated creative practices. Includes multiple perspectives on the value and health benefits of the arts and humanities not limited to or dominated by medicine. Divided into two main sections, the Companion looks at 'Reflections and Critical Perspectives,' offering current thinking and definitions within health humanities, and 'Applications," comprising a wide selection of applied arts and humanities practices from comedy, writing, and dancing to yoga, cooking, and horticultural display."--